ANALISIS PENGARUH EARNINGS PER SHARE DAN DIVIDENS PER SHARE TERHADAP HARGA SAHAM PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - B31110099, Adi Gunawan (Jurnal Manajemen Update, 2013)
This study is performed to examine the effect of Earnings Per Share (EPS) and Dividend Per Share (DPS) toward stock price of companies listed on Index LQ45 BEI over period 2006-2010. Sampling technique used is purposive sampling with criteria; (1) companies listed on the Index LQ45 BEI over period 2006-2010; (2) companies that always pays the dividends over period 2006-2010; and (3) companies that always represents their financial reports over periode 2006-2010. Data that used is secondary data. It is gained sample amount of 13 companies from 45 companies those are listed on Index LQ45. The analysis technique used here is multiple regression and hypothesis test using t-statistic to examine partial regression coefficient and f-statistic to examine simultan regression coefficient. In addition, classical assumption is also performed including normality test, multicolinearity test, heteroscedasticity test, and autocorrelation test. From the analysis result, it indicates that EPS and DPS partially significant toward stock price of companies listed on LQ45 over periode 2006-2010. While simultaneously EPS and DPS proof significantly influent stock price of companies listed on LQ45 over periode 2006-2010. Predictable from EPS and DPS toward stock price of companies is 81,5% as indicated by adjusted R square that is 81,5% while the rest 18,5% is affected by other factors is not included into this study model. Keywords: Earnings Per Share (EPS), Dividend Per Share (DPS), and Stock Price